Perú: la inestabilidad que no acaba - Pinedo-Bravo, Enith (2023)
The social and political crisis Peru has been experiencing in recent years has generated several analyses from different perspectives. This paper will briefly review the characteristics of certain functions of the Congress of the Republic in a Presidential regime. The starting point for this, considering the events of the last seven years, is the analysis of how political impeachment has been exercised through the presidential vacancy due to permanent moral incapacity.